Evaluation of in vitro and in vivo biocompatibility and structure of cobalt-releasing sol-gel bioactive glass. Issue 16 (November 2018) - Barrioni, Breno Rocha; Laia, Andréia Grossi Santos de; Valverde, Thalita Marcolan; Martins, Thaís Maria da Mata; Caliari, Marcelo Vidigal; Sá, Marcos Augusto de; Goes, Alfredo Miranda de; Pereira, Marivalda de Magalhães
Abstract: Cobalt (Co) ions have the potential to improve angiogenesis due to its stabilizing effect on hypoxia-inducible factor 1 (HIF-1α), and its incorporation into bioactive glasses as a therapeutic ion have recently attracted great attention from the research community. However, despite its promising properties, the effect of Co on the glass structure and its biocompatibility is yet to be studied in detail. Therefore, we synthesized a novel sol-gel derived bioactive glass in the SiO2 -CaO-P2 O5 -CoO system, and performed its structural and biological evaluation. Co-containing bioactive glass with high surface area, nanoporosity, amorphous structure, and sustained ion release was obtained. In vitro biocompatibility was confirmed by MTT assay, and no cytotoxicity was observed in human adipose stem cells (hASCs) and human umbilical vein endothelial cells (HUVECs). In vivo responses showed no adverse reactions and indicated the presence of neoformed vessels after bioactive glass implantation in the dorsum of rats, which is the characteristic of a high angiogenesis level due Co release. The results confirmed the biocompatibility of Co-releasing bioactive glass. Thus, Co-incorporation as a therapeutic ion is a potential strategy to obtain superior materials for tissue repair.